Improving Students' Metacognitive Skills and Learning Outcomes Through The Application of Task-Based Learning Model of Direct Instruction - Syahmani Syahmani; Almubarak Almubarak; Nor Aulia Azizah (FKIP ULM, 2023)
The problem of low metacognitive skills and student learning outcomes on colloid topics is overcome by implementing Task-Based Learning Direct Instruction (TBLDI) models. This study aims to improve (1) metacognitive skills, (2) learning outcomes aspects of knowledge, attitudes, and skills, (3) teacher implementation in applying the TBLDI model; (4) student activity. This research was conducted using a classroom action research design in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research subjects were 33 students of class XI IPA 3 at SMA Negeri 10 Banjarmasin. Data was collected using valid instruments, metacognition skills tests (V = 0.98), student learning outcomes tests (V = 0.99), and non-tests to determine the process of implementing actions. Data were analyzed using quantitative and qualitative descriptive techniques. The results of the study showed that (1) students' metacognitive skills increased from the category starting to develop to be well developed, (2) knowledge learning outcomes increased from the less to the good category, attitudes were in a good category, and skills were also in the skilled category in cycle II, (3) the implementation of the teacher in implementing the TBLDI model is very good, (4) the activity of students increases from being active in cycle I to being very active in cycle II.